Trade Policy Reforms in Latin America Multilateral Rules and Domestic Institutions - Lengyel, Miguel F.; Ventura-Dias, Vivianne (Palgrave Macmillan UK, 2004)
This volume examines the interaction between private and public institutions in the trade policy-making process of eight Latin American countries and trade bargaining in sub-regional, hemispheric and multilateral fora. Faced with expanding trade agendas, diversifying negotiation fora, and an uncertain global economy, each country has found its own niche in regional integration and global insertion, providing a wealth of idiosyncratic and convergent policies